O crédito comercial facilita o acesso ao financiamento bancário? Evidências empíricas em empresas listadas na Bovespa - Mello, Eliane de (Universidade do Vale do Rio dos Sinos, 2011)
Financing by suppliers is a subject that has been scarcely studied at the national level. However, in the international literature, several hypotheses have been proposed to explain the different reasons that have led to this phenomenon, called trade credit, which does not seem to be based on a general theory. Organizations have justified the offer of trade credit assuming that, in case of absence of such financing, customers that do not have access to credit from financial institutions could not buy their products. Credit is something very important, and companies that function as financial intermediates play a fundamental role as bank surrogates by offering trade credit to companies that have restrictions in terms of bank credit. Considering all this, the present study aims at examining whether the trade credit facilities the access to bank credit and or it is its surrogate. Considering data from a panel of 322 Brazilian public companies in the period from 2000 to 2009, the results have confirmed the hypothesis of surrogacy. In addition, when tested only in companies with positive net equity, the hypothesis of surrogacy is accepted for younger companies with more assets. The empirical results have also made it possible to admit that, despite older companies having greater debt capacity, they prefer finance themselves through internally generated resources. Besides that, age is highly significant in smaller companies.
Keywords: Crédito comercial; Substituição; Crédito bancário; Restrição financeira; Trade credit; Surrogacy; Bank credit; Financial restriction; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis